CCD photometry and modelling of the ROTSE-1 variable GSC 2534:1121 - Gazeas, K. D.; Manimanis, V. N.; Niarchos, P. G.; Vamvatira-Nakou, C. (Recent Advances in Astronomy and Astrophysics, 2006)
The first VRI CCD photometric observations of the newly discovered ROTSE-1 eclipsing variable GSC 2534:1121 are presented. Our new times of minima are used along with those of the last two years to calculate a new ephemeris of the system. The observed light curves are analyzed with the Wilson-Devinney program in order to derive the geometric and photometric elements of the system. The moderate O'Connell effect is explained by assuming a cool spot on the primary component.
Keywords: 95.55.Aq; 95.55.Qf; 97.80.Fk; 97.80.Hn; Charge-coupled devices image detectors and IR detector arrays; close binaries; Eclipsing binaries; Photometric polarimetric and spectroscopic instrumentation; Spectroscopic binaries